La1-xGdxCr1-yNiyO3 perovskite nanoparticles synthesis by micro-emulsion route: Dielectric, magnetic and photocatalytic properties evaluation. Issue 4 (15th February 2021) - Bibi, Ismat; Maqbool, Humaira; Iqbal, Shahid; Majid, Farzana; Kamal, Shagufta; Alwadai, Norah; Iqbal, Munawar
Abstract: La1-x Gdx Cr1-y Niy O3 nanoparticles were synthesized by micro-emulsion approach. The fabricated NPs were characterized by EDX, SEM, XRD, VSM and UV–Vis techniques. The X-ray diffraction analysis confirmed the successful substitution of Gd 3+ and Ni 3+ ions into the LaCrO3 structure with rhombohedral structure. The lattice parameters, i.e., bulk density, X-ray density, porosity and crystallite size were calculated for doped and undoped LaCrO3 . Morphology of the synthesized NPs shows the aggregation of particles. The average crystallite size determined through XRD and SEM was in the range 30–45 nm. The optical band gaps energy calculated using Tauc plots for undoped and doped material was found to be 2.17 eV–2.03 eV. The Hysteresis study revealed that the magnetization saturation of Gd 3+ and Ni 3+ doped LaCrO3 was greater than un-doped NPs showing the ferromagnetic properties of fabricated materials, which gradually increased by increasing the dopant Gd 3+ and Ni 3+ concentration. Investigation of dielectric properties for doped and undoped materials revealed that the dielectric constant and dielectric loss shows a decreasing trend at higher frequency due to the decrease in various types of polarization. Photocatalytic activities of as-synthesized La1-x Gdx Cr1-y Niy O3 NPs were evaluated by the degradation of crystal violet (CV) dye. It was observed that about 94.39% CV dye was degraded by as synthesized NPs in 45 min of UV light irradiation. The results revealed that doping of Gd 3+ and Ni 3+ in the crystal lattice of LaCrO3 NPs reduces the band gap energy and significantly improves the dielectric and magnetic properties, which make them promising candidates to be used as photo-catalyst for the degradations of toxic textile dyes effluent, and for electronic and microwave devices.